Cytogenotoxicity of shakes added with synthetic microingredients - Moura, Débora Dayane Araujo; Peron, Ana Paula; Veloso, Cleidiane Josefa dos Santos; Silva, Maria Eduarda de Sousa; Santos, Fabelina Karollyne Silva dos; Oliveira, Valtânia Ana de (Ciência e Natura, 2017)
The goal of this study was to evaluate the cytotoxicity and genotoxicity of diet shakes of three brands widely marketed in Brazil, named in this study of A, B and C. Assessments were carried out on root meristem cells of Allium cepa at exposure times 24 and 48 hours. The products (treatments) for A and B were evaluated at concentrations of 0.05; 0.10 and 0.20 g/mL, and C at the concentration 0.08; 0.16 and 0.32 g/mL. The diet products at the three concentrations tested, including those suggested as ideal for consumption by the manufacturers, at the two exposure times considered, were found to have significant antiproliferative effect on the meristems evaluated. However, none of the treatments caused significant cellular changes to the tissues of roots. Thus, the products tested were cytotoxic, but not genotoxic, to root meristem cells of A. cepa. Furthermore, it was observed that in all the treatments performed, in the three concentrations, the majority of the dividing cells were at prophase, not being observed cells at anaphase and telophase. Thus, it is suggested to conduct more in-depth studies on the cytotoxicity of these shakes in physiologically more complex bioassays for the verification and deepening of the data obtained here.